Determination of Standard Rate Constant of Azobenzene in Non-Aquaous Media - Özcan Öztürk, Funda (Asian Journal of Chemistry, 2010)
This study suggests an experiment where the standard heterogeneous rate constant ks can be calculated with the help of cyclic voltammetry data obtained through the cyclic voltammeter technique in the laboratory environment. Suggested experiment was consisted of 4 steps. In the first step electrode reaction was defined by using cyclic voltammetry technique. In the second step of the experiment, adsorption of azobenzene to electrode surface was searched. In the third step, necessary quantitative sizes were calculated to determine the standard rate constant. In the last step, standard rate constant was calculated by using obtained data in the previous steps. This heterogenenous standard rate constant for the reduction was calculated by Klingler Kochi technique. In this study, using the micro platinum electrode, the standard rate constant of the azobenzene was calculated as 0.0309 ± 0.002142.